1996
DOI: 10.1007/bf01858171
|View full text |Cite
|
Sign up to set email alerts
|

Influences of social groups on eating patterns: A study among young adults

Abstract: The purpose of this study was to investigate the extent to which social groups influenced eating patterns among young adults, aged 23-26 years. The analyses are based on a study consisting of 703 individuals with social groups being made up by parents, siblings, partners, friends, and co-workers/fellow students. Perceived norms of social groups and social attachment to these groups were measured. Demographic variables included education, income, marital status, and whether participants had children. These vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…The foremost results of this study indicate that social, attitudinal and lifestyle factors are more important than most other variables in explaining variations in the adolescent market for food. This supports several other studies of general food cognition and behaviour (Axelson, 1986), and also supports one earlier study of eating patterns in Norway (Øygard and Klepp, 1996). These findings also bring some new insight into conflicts between parents and children concerning food preferences (Koivisto and Sjö dén, 1996).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The foremost results of this study indicate that social, attitudinal and lifestyle factors are more important than most other variables in explaining variations in the adolescent market for food. This supports several other studies of general food cognition and behaviour (Axelson, 1986), and also supports one earlier study of eating patterns in Norway (Øygard and Klepp, 1996). These findings also bring some new insight into conflicts between parents and children concerning food preferences (Koivisto and Sjö dén, 1996).…”
Section: Discussionsupporting
confidence: 84%
“…Several models fail to represent the family as an important and autonomous context in which food choices are made (Stratton and Bromley, 1999). A Norwegian study of young adults (aged 23-26 years) indicates that social norms are important, particularly perceived norms of partners (Øygard and Klepp, 1996). According to a review by Rolls (1988), family environment and peers are major determinants for children's and teenagers' food preferences; however, individual variation in preferences can only be partly explained by parental influences.…”
Section: Preferences and Individual Aspectsmentioning
confidence: 98%
“…Study participants acknowledged that family and childhood orientations toward food persisted in their current lives. The study results also are consistent with the view that the college experience is a very dynamic period in which both peers and parents play a role in food and health behaviors (Lau et al, 1990;Birkimer et al, 1996;Oygard and Klepp, 1996;Keane, 1997;Pavis et al, 1998). Food and eating experiences were one part of much larger period of transition in the lives of the players.…”
Section: Life Course Transitions and Dietary Change Life Course Transsupporting
confidence: 92%
“…However, a recent study indicates high stability in measured eating behavior scales during the transition from home to college (Meiselman et al, 1999). Both peers and parents may be important influences on the food practices of college students (Lau et al, 1990;Birkimer et al, 1996;Oygard & Klepp, 1996;Pavis et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Research into group size and eating behaviour shows social facilitation occurs across a range of meals, times, and settings and it has been suggested that eating in the presence of others increases the time spent and the amount of food consumed (de Castro, 1990;Clendenen et al, 1994). Moreover, partner's eating norms are believed to exert one of the strongest influences on eating patterns (Oygard and Klepp, 1996) and marital partners who are more interactive in the area of family food have been shown to have healthier diets (Schafer et al, 1999). The type of social interaction varies across temporal, spatial and activity foci and meals are seen as``opportunity space'' for families to come together and converse (Ochs et al, 1989).…”
Section: Introductionmentioning
confidence: 97%